Astaxanthin nanoemulsion enhances cognitive function and mitigates alzheimer’s disease pathological markers in a streptozotocin-induced rat model / Mazzura Wan Chik - Wan Chik, Mazzura (2024)
Malaysia’s older adults is at risk of Alzheimer's disease (AD) as the country’s population ages rapidly, making it an old-age nation by 2030. AD is characterized by neuronal degeneration, which impairs memory, behaviour, language, and visual-spatial skills. Astaxanthin, a keto-carotenoid molecule, is well-known for its antioxidant activity. Despite its low oral bioavailability, astaxanthin is significant research candidate due to its possible health-promoting qualities such as antioxidant and antiinflammatory. As a result, numerous studies on the protective effect of astaxanthin in chronic diseases are available, but very few actually investigate the protective effects of astaxanthin in nano form (nano-formulated astaxanthin has improved bioavailability, solubility, and stability) against AD-like rodent model. The present study aimed to elucidate the neuroprotective effects of astaxanthin nanoemulsion treatment against a chemically-induced AD-like model as a preventive (astaxanthin nanoemulsion treatment before AD induction) and treatment (astaxanthin nanoemulsion treatment after AD induction) measure by assessing cognitive function, biochemical markers, and histopathological changes in the brain. First, the presence of astaxanthin was measured in distinct brain regions (hippocampus, cortex, and cerebellum) to indicate that the synthesized astaxanthin nanoemulsion could pass the blood-brain barrier and exert its putative neuroprotective benefits. Results indicated that the hippocampus showed a significantly higher concentration of astaxanthin compared to the cortex and cerebellum. Given that the hippocampus is related to memory, detecting astaxanthin in the hippocampus indicating its possible neuroprotective effects in neurological diseases that cause memory impairment. Following that, a chemically-induced AD model was established to imitate the pathophysiology of AD by injecting streptozotocin (STZ) intrahippocampally (bilaterally). STZ injection significantly induced memory impairment, elevated synaptosomal amyloid beta and paired helical filament tau (PHFtau), malondialdehyde, and decreased acetylcholine levels in the hippocampus. The results of STZ injection closely mimic some of the important clinical and cognitive aspects of the disease, thus making it a feasible model for future research into the condition and potential treatments. Finally, the neuroprotective effects of astaxanthin nanoemulsion administration on chemically-induced AD-like rats were investigated as a preventive and treatment strategy. Astaxanthin nanoemulsion significantly improved spatial learning memory (AD treatment study), recognition memory (AD prevention study), and motor function (p < 0.05) in behavioural tests. Furthermore, in both preventive and treatment studies, astaxanthin nanoemulsion significantly decreased the levels of synaptosomal amyloid beta and PHF-tau. Treatment with astaxanthin nanoemulsion reduced lipid peroxidation (AD prevention and treatment studies), neuroinflammation (AD prevention and treatment studies), enhanced acetylcholine (AD treatment study), and neuronal plasticity (AD treatment study). In conclusion, the findings of this study suggest that astaxanthin nanoemulsions offer several potential advantages in the setting of AD. It appears to improve cognitive function, and motor performance while also lowering amyloid beta and PHF-tau levels, resulting in reduced neuroinflammation and acting as a radical scavenger. It also possesses antioxidant and anti-inflammatory properties, which help to treat some of the underlying causes of AD.